Epidemiology of leptospirosis in North-Central Italy: Fifteen years of serological data (2002–2016). (August 2019) - Bertelloni, Fabrizio; Cilia, Giovanni; Turchi, Barbara; Pinzauti, Paolo; Cerri, Domenico; Fratini, Filippo
Graphical abstract: Highlights: Fifteen years of serological data on Leptospira in animals were presented. An increase positivity to Leptospira in last years of investigation was recorded. Rise or fall of some serovars were observed. Some changes in hosts/serovars relations were detected. Abstract: Leptospirosis is a re-emerging bacterial zoonosis. North-Central Italy is characterized by a geographic area that promote Leptospira circulation. Data on sero-epidemiological survey carried out from 2002 to 2016 in North-Central Italy were reported and discussed. Overall, 709 out of the 8488 (8.35%) tested sera were positive for Leptospira at the cut-off titer (1:100) and 218 (2.57%) at higher titer (≥1:400). The highest percentages of positivity was recorded for coypus (22.86%), swine (19.74%) and bovine (13.03%). Pomona and Australis resulted the serogroup more often detected, followed by Sejroe and Icterohaemorrhagiae; while, a low number of positive sera was detected for serogroups Ballum, Canicola and Tarassovi. Percentage of positive sera for each year slightly decreased from 2002 to 2008 and rose from 2009. High percentages of positive reactions were recorded in 2014 (17.23%), 2015 (19.61%) and 2016 (38.05%). In conclusion, the results of this investigation reported an increase of leptospirosis in North-Central Italy. Furthermore, several animals resulted infected as accidental hosts by unusual Leptospira serovars. These data could suggest a change in host range for some serovars, that may promote the adaptation to new hosts.